2019
DOI: 10.3390/s19245348
|View full text |Cite
|
Sign up to set email alerts
|

A GSH Fluorescent Probe with a Large Stokes Shift and Its Application in Living Cells

Abstract: Intracellular GSH is the most abundant non-protein biothiol and acts as a central antioxidant to defend against aging toxins and radicals. Meanwhile abnormal level of intracellular GSH concentration is directly related to some diseases. In this case, detecting intracellular GSH rapidly and sensitively is of great significance. We synthesize a simple fluorescent probe (named GP) which can discriminate GSH from Cys (cysteine) or Hcy (homocysteine) and presents a 50-fold fluorescence increasing. The response time… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…3b, the emission intensity (586 nm) was linearly proportional to the GSH concentration in the range of 0–20 μM ( R = 0.99355), which demonstrated that MITO-PQDNs had the potential ability to detect GSH quantitatively. Compared with other reported probes for GSH detection, 32–36 MITO-PQDNs had higher sensitivity for GSH with a detection limit as low as 253 nM.…”
Section: Resultsmentioning
confidence: 84%
“…3b, the emission intensity (586 nm) was linearly proportional to the GSH concentration in the range of 0–20 μM ( R = 0.99355), which demonstrated that MITO-PQDNs had the potential ability to detect GSH quantitatively. Compared with other reported probes for GSH detection, 32–36 MITO-PQDNs had higher sensitivity for GSH with a detection limit as low as 253 nM.…”
Section: Resultsmentioning
confidence: 84%
“…Previous research has emphasized MDA as an indicator of lipid peroxidation while suggesting that SOD is an enzyme that can eliminate harmful substances produced in the process of oxidative metabolism ( Wang et al, 2019 ). GSH is the most abundant non-protein biothiol and is a central antioxidant to defend against the effects of toxins and free radicals in aging ( Mao et al, 2019 ). 5-HT is a neurotransmitter derived from tryptophan that is synthesized both centrally and systemically ( Sahu et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Both of the above designs introduce a strong electron-absorbing group into the probe structure, and the fluorescence of probe is quenched or resurrected after GSH regulation. There are also some references for the application of this design [103][104][105][106][107][108][109].…”
Section: Fluorescent Nano-probe Design Based On Physiological Properties Of Gshmentioning
confidence: 99%